2013
DOI: 10.1242/jcs.134411
|View full text |Cite
|
Sign up to set email alerts
|

p120-catenin in cancer – mechanisms, models and opportunities for intervention

Abstract: The epithelial adherens junction is an E-cadherin-based complex that controls tissue integrity and is stabilized at the plasma membrane by p120-catenin (p120, also known as CTNND1). Mutational and epigenetic inactivation of E-cadherin has been strongly implicated in the development and progression of cancer. In this setting, p120 translocates to the cytosol where it exerts oncogenic properties through aberrant regulation of Rho GTPases, growth factor receptor signaling and derepression of Kaiso (also known as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 136 publications
2
86
0
Order By: Relevance
“…[22][23][24] Cell membrane-localized Kaiso is associated with p120 catenin bound to E-cadherin and previous studies have shown this complex regulates actin cytoskeletal structures. 28 In this study, we show that RhoH and Kaiso interact and co-localize after SDF-1 stimulation at actin-rich cell protrusion sites in Jurkat cells. SDF-1 is a chemokine known to induce directed cell migration in several haematopoietic cell populations, including lymphocytes and haematopoietic stem cells.…”
Section: Discussionsupporting
confidence: 52%
“…[22][23][24] Cell membrane-localized Kaiso is associated with p120 catenin bound to E-cadherin and previous studies have shown this complex regulates actin cytoskeletal structures. 28 In this study, we show that RhoH and Kaiso interact and co-localize after SDF-1 stimulation at actin-rich cell protrusion sites in Jurkat cells. SDF-1 is a chemokine known to induce directed cell migration in several haematopoietic cell populations, including lymphocytes and haematopoietic stem cells.…”
Section: Discussionsupporting
confidence: 52%
“…FMNL2 is one of the effector proteins of small GTPases, such as Cdc42, and was shown to regulate actin dynamics and cell morphology (Kuhn and Geyer, 2014). In addition to functioning as an important regulator of classic cadherins, p120 is a main regulator of Rho GTPase and thus has a prominent effect on actin dynamics and cell morphology (Schackmann et al, 2013). Whether phosphorylation by TNIK alters the ability of these substrates to regulate actin dynamics will require further studies with phosphoblocking and phosphomimetic mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Although the function of p120ctn and its direct homologs in regulating the actin cytoskeleton via small RhoGTPases is well established (Wolf et al, 2006;Anastasiadis, 2007;Keil et al, 2007;Dohn et al, 2009;Schackmann et al, 2013), much less is known about the role of PKPs in organizing actin fi laments and regulating Rho-GTPases. Keratinocyte cell -cell adhesion and differentiation depends on calcium-mediated and calcium-sensing receptor-mediated RhoA-signaling (Tu & You, 2013).…”
Section: Rho-signalingmentioning
confidence: 99%